The Balance Of Power In The Taiwan Strait: An Assessment - Choon, Yin Sam (Penerbit Universiti Sains Malaysia (USM Press), 2010)
This paper argues that the passage of the Anti-Secession law in March 2005 was a logical step forward by the Chinese to restore what they perceived as an imbalance of power across the Taiwan Strait. A chain of events prior to the bill suggested that Taiwan had gained an upper hand with regards to the Taiwan issue due mainly to the developing US — Taiwan relationship and Taiwan′s strong pro-independence position under the Democratic Progressive Party (DPP). The passage of the Anti-Secession law told the world that China would not allow Taiwan to secede and that the Chinese were willing to fight for this cause. The Chinese have long held the position that Taiwan is part of China. They consider reunification with Taiwan to be a principled issue of national unity, sovereignty and territorial integration of the motherland, an issue of critical importance to China′s national interest. The election of Ma Ying-Jeou as Taiwan′s President in March 2008 was at least marked by a temporary reduction of tension across the straits. However, the new president′s efforts to foster a closer relationship with mainland China have not generated as much of a positive impact. Hence, tension across the Taiwan Strait remains intense.